1995
DOI: 10.1073/pnas.92.15.6930
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human granzyme B promoter regulatory elements interacting with activated T-cell-specific proteins: implication of Ikaros and CBF binding sites in promoter activation.

Abstract: Granzyme B serine protease is found in the granules of activated cytotoxic T cells and in natural and lymphokine-activated killer cells. This protease plays a critical role in the rapid induction of target cell DNA fragmentation. The DNA regulatory elements that are responsible for the specificity of granzyme B gene transcription in activated T-cells reside between nt -148 and +60 (relative to the transcription start point at +1) of the human granzyme B gene promoter. This region contains binding sites for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 39 publications
1
54
1
Order By: Relevance
“…Analysis of reporter assays using promoters that had been systematically mutated at these sites in primary cells and cell lines revealed subtle differences in the importance of some transcription factors in primary cells versus cell lines. For example, AP-1, CREB, and CBF were not as important for transcription in primary cells as they appeared to be in cell lines (37,39). These studies suggested that combinations of transcription factors (particularly AP-1 and CBF) are required to activate GzmB expression in primary cells.…”
Section: Transcriptional Regulation Of Granzymesmentioning
confidence: 74%
See 2 more Smart Citations
“…Analysis of reporter assays using promoters that had been systematically mutated at these sites in primary cells and cell lines revealed subtle differences in the importance of some transcription factors in primary cells versus cell lines. For example, AP-1, CREB, and CBF were not as important for transcription in primary cells as they appeared to be in cell lines (37,39). These studies suggested that combinations of transcription factors (particularly AP-1 and CBF) are required to activate GzmB expression in primary cells.…”
Section: Transcriptional Regulation Of Granzymesmentioning
confidence: 74%
“…The most compelling difference between the mouse and human GzmB gene promoter is the importance of the Ikaros site in human GzmB expression. Mutations introduced into the Ikarosbinding site of the human, but not mouse, GzmB promoter abrogate expression in primary T cells (37,39).…”
Section: Transcriptional Regulation Of Granzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…This domain mediates DNA binding as well as dimerization to PEBP2b/CBFB, which has no direct DNA binding ability, and confers enhanced DNA binding capacity to PEBP2a (Ogawa et al, 1993b;Wang et al, 1993). PEBP2a speci®cally recognizes a consensus sequence, PuACCPuCA and has been reported to control polyoma virus enhancer (Kamachi et al, 1990), murine leukemia virus enhancers , T cell-speci®c genes (Giese et al, 1995;Hallberg et al, 1992;Hsiang et al, 1993;Prosser et al, 1992;Redondo et al, 1992), enzymes (myeloperoxidase, neutrophil elastase, granzyme B serine protease) (Nuchprayoon et al, 1994;Wargnier et al, 1995) and cytokines and their receptors (GM-CSF, IL3, CSF-1) (Cameron et al, 1994;Frank et al, 1995;Zhang et al, 1994). PEBP2aA and ETS1 have been shown to bind together and interact synergistically on the promoter of the T cell receptor a gene (Giese et al, 1995) and T cell receptor b gene (Wotton et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…First, MIF and UVA were found to activate ERK, p38 MAPK, and JNK modules (13,14). Second, MAPK are candidates for the regulation of AP1 and CREB, two regulatory elements of GrB promoter (15,16). Third, we have already demonstrated that UVB induced GrB expression via MAPK pathway in keratinocytes (6).…”
Section: Role Of P38 Mapk In Mif-and Uva-induced Grb Activation-mentioning
confidence: 99%